Math, asked by shardulsumant431, 3 months ago

who will answer my question I will mark as brainliest​

Attachments:

Answers

Answered by abhayshukla10b
2

Answer:

c.) both (a) and (b)

Step-by-step explanation:

p(x)=x²-5x+6

=x²-2x-3x+6

=x(x-2)-3(x-2)

= (x-2)(x-3)

Answered by CopyThat
11

Step-by-step explanation:

v) If equation of parabola is given by, p(x) = x² - 5x + 6, then its factors are c) Both (a) and (b).

⇒ x² - 5x + 6

⇒ x² - 2x - 3x + 6 = 0

⇒ x(x - 2) - 3(x -2) = 0

(x - 2) (x - 3) are the factors of p(x) x² - 5x + 6.

...ッ

Similar questions